Earthworm (Clitellata: Lumbricidae) records from the Rila Mountains (Bulgaria) - HRISTO VALCHOVSKI (ZooNotes, 2016)
The current study is a contribution to the knowledge of the earthworm diversity from the Rila Mountains (Bulgaria). During the investigation 13 earthworm species were collected altogether, belonging to eight genera. Among them Aporrectodea handlirschi (Rosa, 1897) and Aporrectodea caliginosa (Savigny, 1826) proved to be new records from the territory of the Rila Mountain.